Uji Antiangiogenesis Secara In Vivo Ekstrak Etanol Biji Kopi Robusta (Coffea Robusta) dengan Metode Chorio Allantoic Membrane (CAM): Antiangiogenesis Test In Vivo Extract of Robusta Coffee Beans (Coffea robusta) Using Chorio Allantoic Membrane (CAM) Method - Yusuf, Muhammad; Alyidrus, Rugayyah (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
Angiogenesis is a process of forming new capillaries found in the blood vessel system. Angiogenesis plays an important role in tumor growth and metastasis which includes several biological processes. Cancer cells require a supply of nutrients through the blood vessels to grow and develop so that the cancer cells secrete growth substances to stimulate the formation of new blood vessels to meet their nutritional supply. Robusta coffee beans (C.robusta) contain compounds that function as strong antioxidants namely Chlorogenic acid which is a polyphenol group compound that is thought to have antiangiogenesis effects. This study aims to look at the antiangiogenesis potential of robusta coffee bean ethanol extract (C.robusta) with the Chorio Allantoic Membrane (CAM) method and determine the concentration of robusta coffee bean extract (C.robusta) which has the potential as an antiangiogenesis. Antiangiogenesis test using the Chorio Allantoic Membrane (CAM) method using 9-day-old chicken eggs. In this study eggs were divided into 4 groups, group I was the untreated group, groups II, III, IV were groups that were given ethanol extract of robusta coffee beans (C.robusta) with concentrations of 6000 μg/ml, 5500 µg/ml respectively. and 5000 µg/ml. The eggs are re-incubated for 72 hours. In this study, a macroscopic semi-quantitative score was observed. The score data obtained were analyzed statistically by the One Way Anova test. Based on the Saphiro Wilk normality test results, the results of observations of antiangiogenesis in ethanol extracts of Robusta (Coffea robusta) concentrations of 6000 μg/ml, 5500 μg/ml, and 5000 μg/ml obtained a significance value of 0.248 (p>0.05). Continuing the One Way Anova test in the antiangiogenesis test obtained a significance value of 0.007 (p<0.05). Then proceed with the Post Hoc Test. In the test group the concentration of 6000 µg/ml, 5500 µg/ml, and 5000 µg/ml had a value of p>0.05 which means that there were no differences between groups in inhibiting angiogenesis. Based on the results of the study it can be concluded that the ethanol extract of robusta coffee beans (C. robusta) 6000 μg/ml, 5500 μg/ml, and 5000 μg/ml has antiangiogenesis effect on Chorio Allantoic Membrane (CAM) of chicken embryo.